PENINGKATAN POTENSI MAKANAN OLAHAN IKAN DENGAN TEKNIK RESTRUKTURISASI: MINI REVIEW - M Irfan Febriansyah; Nafisah Eka Puteri; Noer Octaviana Maliza; Ernawati Ernawati (Agros Journal of Agriculture Science, 2023)
Fish consumption has been linked to positive effects on health. However, some fish species are overexploited or underutilized due to consumer preferences related to size, taste, odor, color, or texture. To overcome these challenges, restructuring fish products is an important processing technique aimed at modifying the texture, appearance, or physical form of processed fish products. Restructuring enhances product value, consumer appeal, and facilitates easier processing. Restructuring technology not only applies to fish meat but also to by-products, offering positive effects on food availability and reducing environmental waste. Restructuring techniques include enzymatic treatment, hydrocolloid addition, and pressure application, among others. These techniques have been successfully applied to various fish species, resulting in improved product characteristics such as texture, color, gel strength, water-binding capacity, and sensory attributes. By understanding the various techniques and benefits of fish product restructuring, innovative and high-quality processed fish products can be developed to meet consumer preferences while maintaining product quality and sustainability. These studies contribute to the development of the fishing industry, public health, and overall global well-being by enhancing food and non-food product potential and meeting economical needs. INTISARIKonsumsi ikan telah dikaitkan dengan efek positif kesehatan tubuh. Namun, beberapa spesies ikan dieksploitasi berlebihan atau kurang dimanfaatkan karena preferensi konsumen terkait ukuran, rasa, bau, warna, atau tekstur. Untuk mengatasi tantangan ini, restrukturisasi produk ikan yang bertujuan untuk memodifikasi tekstur, penampilan, atau bentuk fisik produk ikan olahan sehingga nilai produk, daya tarik konsumen, dan memudahkan proses pengolahan. Teknologi restrukturisasi tidak hanya diterapkan pada daging ikan tetapi juga pada produk samping, yang menawarkan efek positif pada ketersediaan pangan dan mengurangi limbah lingkungan. Teknik restrukturisasi meliputi perlakuan enzimatik, penambahan bahan hidrokoloid, dan aplikasi tekanan. Teknik ini telah berhasil diterapkan pada berbagai spesies ikan dan menghasilkan peningkatan karakteristik produk seperti tekstur, warna, kekuatan gel, kapasitas pengikat air, dan atribut sensoris. Dengan memahami berbagai teknik dan manfaat restrukturisasi produk ikan, produk ikan olahan yang inovatif dan berkualitas tinggi dapat dikembangkan untuk memenuhi preferensi konsumen dengan menjaga mutu dan keberlanjutan produk. Studi-studi ini berkontribusi pada pengembangan industri perikanan, kesehatan masyarakat, dan kesejahteraan global secara keseluruhan dengan meningkatkan potensi produk pangan dan non-pangan serta memenuhi kebutuhan ekonomi.